The discussion on the function and design of mosque in modern muslim society. - Utaberta, Nangkula; Nadia Malini (Universiti Putra Malaysia Press, 2013)
Although studies on the design of mosque and the true identity of the mosque had been done however the misconception on the true function of the mosque has not been attracting the public. Few studies have examined the role of a mosque and the true Islamic architecture has been done these on the other hand did not capture the nation that are still have their own stereotypical thoughts and idea on the design and what is a mosque. The main objective of this paper is to the function and design of mosque in a modern Muslim society. People neglected the p pray. A mosque should act as civic and political engagement catalyst in mobilization of the religion here and thereafter. The religious house of God plays wider role then just a place for worship. This article will be on the understanding of the true function of mosque.